Characteristics of clinical, laboratory, and immunological manifestations in patients with anticentromere antibody-associated Sjögren's disease - B. D. Chaltsev; V. I. Vasilyev; S. G. Palshina; A. V. Torgashina; E. V. Sokol; Yu. I. Khvan; E. B. Rodionova; T. N. Safonova; S. V. Lapin; O. Yu. Tkachenko; A. V. Mazing (Современная ревматология, 2020)
Objective: to study clinical and laboratory features in patients with anticentromere antibody (ACA)-positive SjЪgren's disease (SD), as well as the sensitivity of different methods for determination of ACA, and to elaborate an algorithm for differential diagnosis in ACA-positive patients.Patients and methods. The V.A. Nasonova Research Institute of Rheumatology followed up 136 patients who were highly positive for ACA. The investigators used the 2001 Russian criteria for the diagnosis for SD; the 2013 ACR/European League Against Rheumatism (EULAR) criteria for that of scleroderma systematica (SDS); the guidelines of the American Association for the Study of Liver Diseases, the Russian Gastroenterological Association, and the Russian Society for the Study of the Liver for that of primary biliary cholangitis (PBC)/biliary duct epitheliitis in the presence of SD. Lymphomas were diagnosed by biopsies of affected organs according to the WHO classification. SD was diagnosed in 119 patients; SDS in 49 cases (37 with SDS concurrent with SD and 12 with isolated SDS), PBC/biliary duct epitheliitis in 23 (all cases with PBC/biliary duct epitheliitis concurrent with SD and/or SDS); 5 patients were excluded from the investigation. Further analysis included 131 ACA-positive patients. The patients were divided into three groups: SD (n=82 or 62.6%); SD+SDS (n=37 or 28.24%); SDS (n=12 or 9.16%).Results and discussion. Autoantibodies to centromere peptide (CENP) A and CENP-B in the same titers were detected in all ACA-positive patients, regardless of diagnosis. Comparative analysis of three patient groups revealed no statistically significant differences in the frequency of laboratory deviations. The signs characteristic of classical SD (rheumatoid factor (RF)), anti-Ro and anti-La antibodies, leukopenia, higher ESR values, hypergammaglobulinemia, and elevated IgG/IgA levels) were found in a small proportion of patients. The frequency and severity of glandular manifestations did not differ in SD and SD + SDS. PBC/biliary duct epitheliitis was present in 17.5% of ACA-positive patients (in most antimitochondrial antibody-positive cases); no statistically significant differences in its frequency were found between the groups. Other extraglandular manifestations in SD and SD + SDS were identified in a smaller number of patients. All sclerodermic spectrum manifestations were more common in SD and SD + SDS than in BS. Pulmonary arterial hypertension was not diagnosed in any patient from the SD group. MALT lymphomas were detected in 19 ACA-positive patients. Those were present only in BS patients and absent in the SDS group. MALT lymphomas developed in the first 10 years after the onset of SD. The transformation of MALT lymphoma into diffuse large B-cell lymphoma was observed in 2 patients. The main signs of lymphomas in SD patients were persistent parotid salivary gland enlargement, decreased levels of complement C4 and peripheral blood CD19+ cells, as well as cryoglobulinemic vasculitis, serum monoclonal secretion, lymphoid infiltration in the minor salivary glands (a focus score of >4), and severe damage to the salivary and lacrimal glands.Conclusion. ACA-associated SD is an independent disease subtype characterized by an increased risk for SDS, PBC, and MALT lymphomas and by a low frequency of the systemic manifestations and laboratory signs characteristic of classical SD. Regardless of the detected type of antibodies and the presence or absence of extraglandular manifestations, damage to the salivary and lacrimal glands progresses in SD, which often leads to lymphomas; therefore, the therapy that may prevent this complication should be initiated as soon as possible after SD diagnosis. The lymphoproliferation signs identified in this investigation should be taken into account in all ACA-positive patients with SD for the early diagnosis of lymphoid tumors before therapy is prescribed. An algorithm for differential diagnosis in seropositivity for ACA is presented. Determination of autoantibodies to CENP-A and CENP-B does not allow the differential diagnosis in ACA-positive patients.